2019
DOI: 10.1016/j.jtumed.2019.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Antihyperglycaemic and tissue-repair effects of Myrmeleon formicarius extract in streptozotocin-induced diabetic mice

Abstract: Objectives In this study, we aimed to investigate the effects of oral administration of Myrmeleon formicarius (antlion) extract on liver and kidney histology in streptozotocin-induced diabetic mice. Methods Twenty-four mice received a single intraperitoneal injection of streptozotocin and were then divided into six groups. Untreated diabetic mice served as the negative control group, and glibenclamide-treated mice served as the positive contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…It was previously demonstrated that there are pathological changes in hepatic tissue of STZ-induced T2DM mice, including focal necrosis, lymphocyte infiltration, obvious congestion in the central vein, and so on. 43,44 In this study, we observed histopathological changes in the liver and the results are presented in (Fig. 6A).…”
Section: Effect Of Lnt-1 On Histomorphological Changes Of Mouse Liver...mentioning
confidence: 57%
“…It was previously demonstrated that there are pathological changes in hepatic tissue of STZ-induced T2DM mice, including focal necrosis, lymphocyte infiltration, obvious congestion in the central vein, and so on. 43,44 In this study, we observed histopathological changes in the liver and the results are presented in (Fig. 6A).…”
Section: Effect Of Lnt-1 On Histomorphological Changes Of Mouse Liver...mentioning
confidence: 57%
“…Based on a research by Prihatin Jekti, it can be known that the comparison between doses 2.5, 7.5 and 10 mg/kg are significant in lowering blood glucose level, but there was no significant differences between those doses. 10 From this study, it can be known that treatment group 1 (P1) is the group that had the most significant decrease of blood glucose level on the 28 th day seen from its p value <0.001, smaller than p value =0.0034 in treatment group 3 (P3). This result is in line with a research conducted by Tyas Kurniasih (2006) which showed that the administration of antions juice dosed 0.01 mg/200 g mice body weight can lower the blood glucose level in hyperglycemic mice (p<0.05).…”
Section: Discussionmentioning
confidence: 78%
“…The study showed that antlion extract treatment resulted in minimal damage in kidney and liver at 5 and 10 mg/ kg BW respectively. In the study, another compound present in antlion larvae extract is a chaperone protein that can stimulate cell regeneration (Prihatin et al, 2019). Heat Shock Protein (HSP) HSP70 is the most common HSP in humans that could inhibit TNF-αinduced free radical formation, lipid peroxidation, and apoptosis (Ikwegbue et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Heat Shock Protein (HSP) HSP70 is the most common HSP in humans that could inhibit TNF-αinduced free radical formation, lipid peroxidation, and apoptosis (Ikwegbue et al, 2018). Thus, chaperone protein present in antlion extract can also take effect in its tissue-repair ability (Kumar et al, 2014;Prihatin et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation